Foxp3⁺ regulatory T cells delay expulsion of intestinal nematodes by suppression of IL-9-driven mast cell activation in BALB/c but not in C57BL/6 mice. - Birte Blankenhaus (Public Library of Science (PLoS), 2014)
Accumulating evidence suggests that IL-9-mediated immunity plays a fundamental role in control of intestinal nematode infection. Here we report a different impact of Foxp3⁺ regulatory T cells (Treg) in nematode-induced evasion of IL-9-mediated immunity in BALB/c and C57BL/6 mice. Infection with Strongyloides ratti induced Treg expansion with similar kinetics and phenotype in both strains. Strikingly, Treg depletion reduced parasite burden selectively in BALB/c but not in C57BL/6 mice. Treg function was apparent in both strains as Treg depletion increased nematode-specific humoral and cellular Th2 response in BALB/c and C57BL/6 mice to the same extent. Improved resistance in Treg-depleted BALB/c mice was accompanied by increased production of IL-9 and accelerated degranulation of mast cells. In contrast, IL-9 production was not significantly elevated and kinetics of mast cell degranulation were unaffected by Treg depletion in C57BL/6 mice. By in vivo neutralization, we demonstrate that increased IL-9 production during the first days of infection caused accelerated mast cell degranulation and rapid expulsion of S. ratti adults from the small intestine of Treg-depleted BALB/c mice. In genetically mast cell-deficient (Cpa3-Cre) BALB/c mice, Treg depletion still resulted in increased IL-9 production but resistance to S. ratti infection was lost, suggesting that IL-9-driven mast cell activation mediated accelerated expulsion of S. ratti in Treg-depleted BALB/c mice. This IL-9-driven mast cell degranulation is a central mechanism of S. ratti expulsion in both, BALB/c and C57BL/6 mice, because IL-9 injection reduced and IL-9 neutralization increased parasite burden in the presence of Treg in both strains. Therefore our results suggest that Foxp3⁺ Treg suppress sufficient IL-9 production for subsequent mast cell degranulation during S. ratti infection in a non-redundant manner in BALB/c mice, whereas additional regulatory pathways are functional in Treg-depleted C57BL/6 mice.